Care experiences of young people with eating disorders and their parents: qualitative study. Issue 1 (January 2019) - Mitrofan, Oana; Petkova, Hristina; Janssens, Astrid; Kelly, Jonathan; Edwards, Eve; Nicholls, Dasha; McNicholas, Fiona; Simic, Mima; Eisler, Ivan; Ford, Tamsin; Byford, Sarah
Abstract : Background: Perspectives of young people with eating disorders and their parents on helpful aspects of care should be incorporated into evidence-based practice and service design, but data are limited. Aims: To explore patient and parent perspectives on positive and negative aspects of care for young people with eating disorders. Method: Six online focus groups with 19 young people aged 16–25 years with existing or past eating disorders and 11 parents. Results: Thematic analysis identified three key themes: the need to (a) shift from a weight-focused to a more holistic, individualised and consistent care approach, with a better balance in targeting psychological and physical problems from an early stage; (b) improve professionals' knowledge and attitude towards patients and their families at all levels of care from primary to 'truly specialist'; (c) enhance peer and family support. Conclusions: Young people and parents identified an array of limitations in approaches to care for young people with eating disorders and raised the need for change, particularly a move away from a primarily weight-focused treatment and a stronger emphasis on psychological needs and individualised care. Declaration of interest: None.